The Fantasy Film - Maldonado-DeOliveira, Débora (Imagofagia, 2021)
Sobre Fowkes, Katherine A. The Fantasy Film. West Sussex,. West Sussex, UK, Wiley-Blackwell, 2010, 216 pp., ISBN 978-1405168793. Palabras clave: reseña, Katherine A. Fowkes, The Fantasy Film